Народное ополчение защищает Родину - Головко, М. Л.; Рященко, Д. С.; Сушко, О. О. (Український історичний журнал, 2025)
П. В. Добров, А. Д. Колесник, Г. А. Куманев, Е. Я. Пашко. НАРОДНОЕ ОПОЛЧЕНИЕ ЗАЩИЩАЕТ РОДИНУ. М.: Наука, 1990. — 384 с.